2021
DOI: 10.3390/cancers13071527
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase Expression in Multiple Myeloma Associates with Disease Progression and Sensitivity to Melflufen

Abstract: Multiple myeloma (MM) is characterized by extensive immunoglobulin production leading to an excessive load on protein homeostasis in tumor cells. Aminopeptidases contribute to proteolysis by catalyzing the hydrolysis of amino acids from proteins or peptides and function downstream of the ubiquitin–proteasome pathway. Notably, aminopeptidases can be utilized in the delivery of antibody and peptide-conjugated drugs, such as melflufen, currently in clinical trials. We analyzed the expression of 39 aminopeptidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Many biological processes involve these proteins, including cancer cell defense against oxidative stress. A previous study demonstrated that DPP3 and DPP7 are highly expressed in multiple myelomas [ 13 ]. DPP3 overexpression was positively associated with KEAP1 mutant tumors, and it further promoted lung cancer development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many biological processes involve these proteins, including cancer cell defense against oxidative stress. A previous study demonstrated that DPP3 and DPP7 are highly expressed in multiple myelomas [ 13 ]. DPP3 overexpression was positively associated with KEAP1 mutant tumors, and it further promoted lung cancer development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data confirm inferior survival of MM patients with higher RNPEP gene expression, observed in an independent cohort of patients published elsewhere. 34 Together, these data suggest association of ApB with BTZ-resistance and poor prognosis in MM.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, elevated RNPEP gene expression is associated with a shorter progression-free and overall survival of MM patients, thus confirming higher RNPEP expression as a risk factor previously described in other patient cohorts. 34 Likewise, elevated RNPEP gene expression is observed in plasma cell precursors, a B-lymphoid cell compartment, where the tumor-initiating MMPC or “stem” cells are residing. 41 Hence, elevated ApB levels are associated with aggressive myeloma clones conferring tumor initiation and therapy resistance in MM.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that a detailed study on aminopeptidase gene expression in myeloma revealed that some aminopeptidases were highly expressed in MM. 46 Moreover, the high expression of some of these aminopeptidase genes, ie, X-prolyl aminopeptidase 1 (XPNPEP1), Arginyl aminopeptidase (RNPEP), Dipeptidyl peptidase 3 (DPP3), and Bleomycin hydrolase (BLMH), was significantly associated with shorter overall survival. More importantly, hydrolysis analysis demonstrated that melflufen is a substrate of Leucine aminopeptidase 3 (LAP3), leukotriene A4 hydrolase (LTA4H), arginyl aminopeptidase (RNPEP), other than aminopeptidase N (ANPEP alias CD13), suggesting that CD13 is not the unique melflufen target in MM.…”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 99%